Enhancing the Mechanical and Physical Properties of Zirconium Dental Filling Material by Chemical Mixing with Polyvinyl Alcohol Polymer in Different Cure Times - Manar Abd Alrazaq Hassan (Diyala Journal of Medicine, 2025)
Background: Zirconium is mainly composed of zirconia/silica particles. Zircon filling material is a light-curing, radiopaque nanohybrid composite resin designed for anterior and posterior tooth restorations with a high inorganic filler component. One synthetic polymer that dissolves in water is polyvinyl alcohol. Polyvinyl Alcohol's low toxicity, low propensity for protein adhesion, and biocompatibility make it useful in a range of medical applications. Contact lenses, eye drops, and cartilage substitutes are among the specific applications. Objectives: evaluate the effect of chemical mixing polyvinyl alcohol polymer on the hardness, strength, water solubility, and water sorption properties of zircon dental filling material. Patients and Methods: The biocomposite was prepared by dissolving 5g of polyvinyl alcohol in distilled water and stirring the mixture continuously for 30 minutes at 80°C. The mixture was stirred until a gel formed. Then, the mixed Universal Restorative material with zircon fillings was exposed to visible violet curing light for hardening, with different curing times (1, 2, 5, 10, 15, and 20 seconds). Then, we measured the strength, hardness, sorption, and solubility of the new mixed filling. Results: Showed an increase in the hardness and the strength of the zircon filling materials after chemical mixing with Polyvinyl Alcohol polymer, compared with traditional zircon material that cured without Polyvinyl Alcohol polymer, and a decrease in the solubility and sorption of the filling material after chemical mixing. Conclusion: An addition of polyvinyl Alcohol polymer particles to impact light-cure zircon dental filling material improves the impact physical and mechanical properties of the new mixed filling material. Keywords: Zirconium, Nanohybrid, Polyvinyl alcohol polymer, Strength, Hardness, Sorption, Solubility.